Social Entrepreneurship and Its Impact on Agriculture in Malaysia - Binti Jaffri, Nurul Fatiha; Thamrin, Husni (Journal of Peasants' Rights, 2024)
This article explains the practice of social entrepreneurship and its impact on agriculture in Malaysia using a critical and systematic qualitative research approach. Several sources used are the researcher's direct experience, books, journals, and other scientific works. The results of the study indicate that social entrepreneurship has been able to provide a positive impact on agriculture in Malaysia, including being able to overcome systematic challenges, including low income, unsecured environmental quality, and sustainable social entrepreneurship development in developing solutions that empower farmers and rural communities so that a balance is created between the lives of rural communities and the lives of urban communities that are often considered unrelated to each other.